Biochar Addition Reduces the Effect of High Nitrogen on Soil–Microbial Stoichiometric Imbalance in Abandoned Grassland on the Loess Plateau of China - Shuainan Liu; Mingjun Xie; Wende Lu; Xinyue Zhang; Mengyin Du; Yao Yao; Jianyu Yuan; Guang Li (Ecology and Evolution, 2025)
ABSTRACT Progressively higher atmospheric nitrogen (N) deposition increasingly affects soil ecosystems' elemental cycling and stability. Biochar (BC) amendment has emerged as a possible means of preserving soil system stability. Nevertheless, the pattern of soil–microbial nutrient cycling and system stability in response to BC after high N deposition in ecologically sensitive regions remains uncertain. Therefore, we investigated the effects of high N (9 g N·m−2·a−1), BC (0, 20, 40 t·ha−1), and combinations of the treatments on soil organic carbon (SOC), total nitrogen (TN), total phosphorus (TP), microbial biomass carbon (MBC), nitrogen (MBN), phosphorus (MBP), microbial entropy (qMB), and stoichiometric imbalance (Cimb:Nimb:Pimb). We found that high N addition decreased topsoil (0–20 cm) TP, C:N, qMBN, and Cimb:Nimb values and increased TN, C:P, N:P, qMBP, Cimb:Pimb, and Nimb:Pimb values. However, BC addition increased 0–40 cm soil qMBC and Nimb:Pimb values and decreased qMBN, Cimb:Nimb, and Cimb:Pimb values. Meanwhile, high BC additions attenuated BC's promotion of soil–microbial nutrients. We observed that a mixture of high N and BC increased the 0–40 cm SOC and TP content, promoted the accumulation of MBN and MBP in the subsoil (20–40 cm), and decreased the topsoil Cimb:Pimb and Nimb:Pimb values compared to high N additions. The impact of high N and BC additions on N and P elements varied significantly between the different soil depths. In addition, redundancy analysis identified C:N, MBC, MBN, and C:P as pivotal factors affecting alterations in soil qMB and stoichiometric imbalance. Overall, adding BC reduced the negative impacts of high N deposition on the stability of soil–microbial systems in the Loess Plateau, suggesting a new approach for managing ecologically fragile areas.